The potential of biological control on invasive weed species - Kabashi, Besarta; Massimi, Mohunnad; Radócz, László (Acta Agraria Debreceniensis, 2023)
Sorghum halepense is one of the invasive species in Europe. This study was made to identify the morphology of fungi on invasive weed species samples on the roots of Sorghum halepense. The samples were collected in the region of Debrecen. The experiment was conducted under laboratory conditions to determine the microscopic form of fungi. The samples were put on PDA and for identification of fungi is based on the morphological characteristics of the features and colonies of conidia that were developed in Petri dishes. The examination of the culture revealed that the fungus from the root of Sorghum halepense was Aspergillus niger. Pathogenicity and the relationship between the fungus and Sorghum halepense are still uncertain so in the future pathogenicity tests and re-isolations from plants are very important steps.